1963
DOI: 10.1021/jf60127a020
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Materials, Preparation and Characterization of Some Calcium Pyrophosphates

Abstract: IV. Morphological and Optical Properties of Crystalline Pyrophosphates Refractive Crystal System, Class, and Habit Indices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 5 publications
(7 reference statements)
8
57
0
Order By: Relevance
“…Crystal-induced inflammation is a dose-related phenomenon (1 4,15), and amounts of synthetic MSU or CPPD crystals in the milligram range are generally injected to induce clinically apparent inflammatory signs and symptoms. It is interesting that the concentrations of HA crystals estimated by the present study are in the microgram range, as is true for CPPD crystals (1 2).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal-induced inflammation is a dose-related phenomenon (1 4,15), and amounts of synthetic MSU or CPPD crystals in the milligram range are generally injected to induce clinically apparent inflammatory signs and symptoms. It is interesting that the concentrations of HA crystals estimated by the present study are in the microgram range, as is true for CPPD crystals (1 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for experiments to detect cytochrome C reduction by crystals, a different MSU preparation that had an average length of 7 p was also used. Calcium pyrophosphate dihydrate (CPPD) crystals were prepared by the method of Brown et al (7). The length of the average CPPD crystal was 8p.…”
Section: Methodsmentioning
confidence: 99%
“…Brown et al 22 have reported a synthetic route to an amorphous calcium pyrophosphate, but with high levels of sodium contamination. Here, we therefore report the synthesis and characterisation of a series of amorphous pyrophosphate phases of O. Syntheses were also attempted where the metal salt solutions were slowly added to a vigorously stirred potassium pyrophosphate solution using the same concentrations as stated previously.…”
Section: Introductionmentioning
confidence: 99%